Employment in Ontario’s Industrial Heartland: Evidence of Economic Decline in a Mid-Sized Industrial City - Kerr, Don; Qiyomiddin, Komin (Canadian Journal of Regional Science / Revue canadienne des sciences régionales, 2021)
As the “second wave” of globalization commenced in the late 1970s and early 1980s, countries around the world underwent economic restructuring. Canada, as one of the nodes in an integrated global economy, was no exception. In particular, the province of Ontario, which was and still is the biggest manufacturing hub in Canada, experienced a decline in terms of manufacturing employment. Inevitably, for London, a mid-sized industrial city located in Southwestern Ontario, this transition had major implications, a reality that it shared with several other cities in the southwest. As closely integrated with the broader North American economy, London’s loss of jobs due to outsourcing and other technological and global forces was certainly not unique. Yet as demonstrated in this paper, London’s labour market has performed particularly poorly since 2001 relative to most other census metropolitan areas (CMAs) across Ontario, or for that matter, across Canada. This is true in terms of overall levels of job creation, as well as growth in the types of jobs that are generally considered desirable in the 21st century, i.e. jobs in higher skilled occupational categories.